Continuous reading experience for the improvement of reading comprehension in Peruvian students - Rosales-Veítia, José Andres (2022)
One of the indicators to measure that students learn so much in schools is called Learning Poverty, and it is related to reading comprehension problems. Therefore, the research aimed to determine the effectiveness of a teaching strategy of continuous reading for improving the read-ing comprehension of students of VI cycle of two educational institutions private in the district of Chorrillos, Lima – Peru. We worked with 94 students of 1st and 2nd high school chosen in a cen-sus sampling, to whom a test was applied at two times (pretest and posttest), divided by an educa-tional intervention that used the tale of The Little Prince to promote continuous reading, additional-ly the test of the ranges with Wilcoxon's sign was used to give statistical validity to the results, which show an average improvement between 60 and 80%, concluding that the strategy is highly effective.